Getting Party Activists on Local ListsHow Dutch Local Party Branches Perform Their Recruitment Function - Otjes, Simon; Boogers, Marcel; Voerman, Gerrit (Politics of the Low Countries, 2020)
This article examines what explains the performance of Dutch local party branches in the recruitment of candidates for municipal councils. Fielding a list of candidates is the most basic function of political parties. In the Netherlands, party branches are under pressure from the low number of party members. To analyse how branches fulfil their role in recruitment, we employ our own survey of the secretaries of party branches held in the run-up to the 2018 municipal election. We find that party membership drives the successful fulfilment of the recruitment function but that, more than the absolute number of members, the crucial factors are how these party members cooperate, the number of active members and the development of this number.